Komunikasi Keluarga: Konsep Suami Membangun Keharmonisan Pasangan Muslim - Alen Manggola (Al-MUNZIR, 2021)
This study aims to determine the description of the form of communication between husbands and wives to build family harmony above understanding. Furthermore, to study, understand and analyze the rights of a wife, this study uses qualitative methods with analysis of literature reviews, documentation studies, and literature studies of relevant previous research results. The results showed that there were three biggest triggers for divorce; 1). Economic factors (material rights), 2). Distance and time factors (non-material rights), 3). Controversy factor (non-material rights). So from the analysis carried out, it can be concluded that the form of communication that must be done by husbands is to provide understanding and motivation of gratitude to their wives for what they have strived for. Because, harmony will be created if mutual understanding, and a husband understands the rights of the wife who are guided by Islamic law.Keywords: Communication, Family, HarmonyAbstrakPenelitian ini bertujuan untuk mengetahui deskripsi bentuk komunikasi suami terhadap isterinya untuk membangun keharmonisan keluarga diatas pengertian. Selanjutnya untuk mengkaji, memahami dan menganalisis hak-hak seorang isteri, penelitian ini menggunakan metode kualitatif dengan analisis kajian pustaka, studi dokumentasi, dan studi literatur terhadap hasil penelitian terdahulu yang relevan. Hasil penelitian menunjukan bahwa pemicu terbesar dari perceraian ada tiga; 1). Faktor ekonomi (hak materi), 2). Faktor jarak dan waktu (hak nonmateri), 3). Faktor pertengkaran (hak nonmateri). Sehingga dari analisa yang dilakukan di peroleh kesimpulan bahwa bentuk komunikasi yang mesti dilakukan para suami adalah dengan memberikan pemahaman dan motivasi syukur terhadap isterinya atas apa yang telah diupayakan. Sebab, keharmonisan akan tercipta apabila saling pengertian, dan seorang suami memahami hak-hak isteri yang berpedoman pada syari’at Islam.Kata Kunci: Komunikasi, Keluarga, Keharmonisan